2004
DOI: 10.2207/qjjws.22.125
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hydrogen Embrittlement Susceptibility of High Strength Steel Based on Local Approach

Abstract: In order to evaluate the hydrogen embrittlement susceptibility of high strength steel independently of stress concentration factor Kt and specimen size, Local Approach method modified to evaluate the hydrogen content distribution in the specimen was used. In the method it was considered that the size of micro cracks depends on the hydrogen content. The stepwise hydrogen embrittlement tests were carried out to obtain the hydrogen embrittlement susceptibility of the material which was 1400 MPa grade JIS SCM440 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…(1) Stepwise Test under Low Applied Stress Condition 17,18) Hydrogen charging, Cd coating, and a hydrogen content homogenizing treatment of the specimens were conducted by the same procedure as the constant loading test. The current density was 1 A/m 2 and the hydrogen charge was for 5 h. In the first step, a stress of 702 MPa was applied on the specimens for 12 h. The specimens that fractured in this step were not used for the evaluation.…”
Section: Hydrogen Embrittlement Test With Stepwise Load-mentioning
confidence: 99%
See 3 more Smart Citations
“…(1) Stepwise Test under Low Applied Stress Condition 17,18) Hydrogen charging, Cd coating, and a hydrogen content homogenizing treatment of the specimens were conducted by the same procedure as the constant loading test. The current density was 1 A/m 2 and the hydrogen charge was for 5 h. In the first step, a stress of 702 MPa was applied on the specimens for 12 h. The specimens that fractured in this step were not used for the evaluation.…”
Section: Hydrogen Embrittlement Test With Stepwise Load-mentioning
confidence: 99%
“…The hydrogen content distribution in the specimens was calculated by Eq. (1) 7,18) ........ 1where Ds h(element) is the difference in the hydrostatic stress of each element and the hydrostatic stress of the element which has an almost uni-axial stress condition that is located 20 mm away from the notched region. DV is the partial molar volume of the hydrogen in bcc-Fe (2ϫ10 Ϫ6 m 3 /mol), R the gas constant, T the test temperature (ϭ300 K), and H the diffusible hydrogen contents of the specimens.…”
Section: Hydrogen Distribution Analysis In Specimensmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the methods of evaluating the delayed fracture characteristics irrespective of the specimen configuration were studied. [2][3][4]7,8) Wang et al [2][3][4] have demonstrated by the slow strain rate test (SSRT) that the relationship between the maximum principal stress and instantaneously accumulated hydrogen concentration at the fracture initiation point during the test is independent of the notch geometry.…”
Section: Introductionmentioning
confidence: 99%